Interrelationship of MMP-9, Proteoglycan-4, and Inflammation in Osteoarthritis Patients Undergoing Total Hip Arthroplasty - Slovacek, Hannah; Khanna, Rajan; Poredos, Pavel; Poredos, Peter; Jezovnik, Mateja; Hoppensteadt, Debra; Fareed, Jawed; Hopkinson, William (Clinical and applied thrombosis/hemostasis, 2021)
Osteoarthritis (OA) is a chronic condition marked by joint pain, inflammation and loss of articular cartilage, that can be treated with total joint arthroplasty (TJA) at end stages. TJA is marked by post-operative inflammation, which directly effects levels of cartilage degradation biomarkers, proteoglycan-4 (PRG4) and matrix metalloproteinase-9 (MMP-9). PRG4 is a protective glycoprotein that is decreased in individuals with OA. MMP-9 is a matrix metalloproteinase that contributes to articular cartilage loss and is elevated in OA patients. It is upregulated by pro-inflammatory markers, such as IL-1, IL-6 and CRP. This study aims to elucidate the immediate post-operative changes in levels of PRG4, MMP-9, IL-6, CRP, and WBC in patients undergoing TJA to clarify the role of inflammation in recovery after surgery and in the overall pathogenesis of OA. Blood was collected at 3 time points (day 0, day 1 post-operatively, and days 5-7 post-operatively), from 63 patients undergoing TJA due to OA, and levels of these biomarkers were quantified. IL-6, CRP, WBC and MMP-9 were lowest at day 0, highest at day 1, and stabilized at an intermediate level at days 5-7. Meanwhile, PRG4 followed the opposite trend. These studies suggest that IL-6, CRP and WBC showed predictable fluctuations, with pro-inflammatory biomarkers upregulating MMP-9 and downregulating PRG4. Measuring these biomarkers may help expose the role of inflammation in the post-surgical recovery of TJA patients and in long-term pathogenesis of OA. These levels may help risk stratify patients pre-operatively and help develop individualized post-surgical plans.